Backside defect evaluation in carbon steel plate using a hybridized magnetic flux leakage and eddy current technique - Mohd Aufa Hadi Putera, Zaini; Mohd Mawardi, Saari; Nurul A’in, Nadzri; Zulkifly, Ab Aziz; Kiwa, Toshihiko (Springer, 2024)
The challenges inherent in effective nondestructive evaluation of backside defects in steel, such as cracks, arise from the limited penetration of eddy currents (EC) due to the high permeability of steel. While the magnetic flux leakage (MFL) technique is able to detect deep defects, it lacks detailed geometry information. In this study, a hybrid approach is proposed, involving the simultaneous analysis of MFL and EC signals using a custom-designed magnetic probe. The probe is developed based on Finite Element Method simulations, followed by validation on 2 mm carbon steel plates containing artificial slits. The simulation results showed that the spatial and intensity responses of MFL and EC signals within the slits can be utilized for characterizing the slits. Furthermore, validation with fabricated backside slits confirms the correlation between slit depth, length and the intensity of the measured signals, particularly when an optimized excitation frequency is employed. The proposed method enables the prediction of slit depth and identification of slit shapes, thereby resulting in an enhancement of backside defect detection capabilities. Through this proposed hybrid technique, a connection is established between MFL and EC methods to enable a versatile tool for the precise assessment of cracks.